Mythical discoveries, utopian spaces and post-socialist culture - Erjavec, Aleš (Filozofski vestnik, 1993)
The authors present different perceptions of the former socialist countries as they arise from different cultural and political frameworks
Keywords: Amerika; art; culture; Europe; Evropa; kultura; postsocializem; umetniki; umetnost